1984
DOI: 10.1017/s0022172400064561
|View full text |Cite
|
Sign up to set email alerts
|

An extended model for transfer of micro-organisms via the hands: differences between organisms and the effect of alcohol disinfection

Abstract: SUMMARYA model for contact transfer of micro-organisms by hand has been extended to include representatives of bacterial species responsible for a majority of hospitalacquired infections. The ability of the organisms to transfer from contaminated fabrics to hands and from hands to sterile fabrics was measured, as was their ability to survive on the skin of the hands. There were differences between the species. Staphylococcus saprophyticus transferred well to the hand but not as well from hand to fabric as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 14 publications
3
88
1
2
Order By: Relevance
“…Mackintosh found that application of 0.3 mL to the hands was no more effective than plain soap-and-water hand washing. 45 Simply increasing the volume to 0.5 mL increased the effectiveness of alcohols substantially. Larson demonstrated that 1 mL of alcohol was significantly less effective than applying 3 mL to the hands.…”
Section: Infection Control and Hospital Epidemiology July 2000mentioning
confidence: 99%
“…Mackintosh found that application of 0.3 mL to the hands was no more effective than plain soap-and-water hand washing. 45 Simply increasing the volume to 0.5 mL increased the effectiveness of alcohols substantially. Larson demonstrated that 1 mL of alcohol was significantly less effective than applying 3 mL to the hands.…”
Section: Infection Control and Hospital Epidemiology July 2000mentioning
confidence: 99%
“…These include bacteria type, source and destination surfaces, time post inoculation, and moisture level. 10,11 Montville et al 12 investigated bacterial transfer rates from food to hands and from hands to food with and without a glove barrier. 12 The authors found that a glove barrier can decelerate the transfer rate of microorganisms from food to hands.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, only 0.06% of the organisms obtained from the contaminated donor fabric were transferred to the recipient fabric via hand contact. Using the same experimental model, Mackintosh and colleagues 169 found that S. saprophyticus, P. aeruginosa, and Serratia spp. were transferred in greater numbers than was E. coli from a contaminated to a clean fabric following hand contact.…”
Section: Experimental Modelsmentioning
confidence: 97%
“…179 A few studies have examined the ability of alcohols to prevent the transfer of health care-associated pathogens by using experimental models of pathogen transmission. 74,88,169 Ehrenkranz and colleagues 88 found that Gram-negative bacilli were transferred from a colonized patient's skin to a piece of catheter material via the hands of nurses in only 17% of experiments following antiseptic handrub with an alcohol-based hand rinse. In contrast, transfer of the organisms occurred in 92% of experiments following handwashing with plain soap and water.…”
Section: Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation